The Concept Of Education In The Qur'an: A Critical Study Of Al-Ghazali's Thinking - Izza Nazalia; Lailatul Fitria (Didaktika: Jurnal Kependidikan, 2024)
This article discusses the concept of education in the Al-Quran from Al-Ghozali's perspective. The research method used by researchers is to use a literature review. This research uses subjective procedures with a descriptive qualitative approach. Based on the results of the literature analysis, it can be concluded that, according to Al-Ghazali, good education is a way to get closer to Allah and gain happiness in this world and the hereafter. Al-Ghazali combines happiness in this world and happiness in the afterlife. In Al-Ghazali's view, educational goals consist of two, namely long-term goals and short-term goals. The curriculum phasing formulated by Al-Ghazali is in accordance with the children's education process taught by Muhammad Rasulullah SAW. Meanwhile, according to Al-Ghazali, educational methods are religious education methods and moral education methods. There are different explanations of education in the Qur'an which basically have one unity in the educational process so that they are able to navigate current and future life.